The Effect of Perceived Quality, Perceived Enjoyment, and Social Influence toward Brand Loyalty of Valorant - Alexander, Jonathan; Hidayat, Desman (Journal of Business, Management, and Social Studies, 2022)
ABSTRACT The purpose of the study was to reveal if there exists a quality-enjoyment-social influence-satisfaction-loyalty gap among gamers when it comes to playing the game Valorant. The study used a deductive and quantitative research approach by conducting an online survey which was distributed with a non-probability convenience sampling technique toward Valorant game players in Indonesia. The survey resulted in 96 valid responses which was quantitatively analyzed. The findings revealed that there exists a quality-enjoyment-social influence-satisfaction-loyalty gap among gamers in Indonesia when it comes to the context of the game Valorant. The most influential determinant affecting customer satisfaction was perceived enjoyment, and the most affecting loyalty was perceived quality. The suggested e-sports experience will contribute to the growing body of knowledge aimed at understanding e-sports consumer behavior.